2004
DOI: 10.1080/15459620490452004
|View full text |Cite
|
Sign up to set email alerts
|

Historical Estimation of Exposure to 1,3-Butadiene, Styrene, and Dimethyldithiocarbamate Among Synthetic Rubber Workers

Abstract: Quantitative estimates of exposure to 1,3-butadiene (BD), styrene (STY), and dimethyldithiocarbamate (DMDTC) were developed for a follow-up study of workers at six North American synthetic rubber plants. Procedures entailed identifying tasks and jobs involving exposure, identifying factors influencing historical changes in exposure potential, and using mathematical models to calculate job- and time-period-specific exposures. Exposure metrics included 8-hour time-weighted average (TWA) intensity, the annual num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 19 publications
(30 reference statements)
1
39
0
Order By: Relevance
“…These 1995 data were updated in 2000 [5,6] to include substantially revised estimates of exposure. The most recent update of the data was in 2004, when the UAB added seven more years of follow-up (through 1998) and included the most recent estimates of exposures developed in 2000 [14,18]. Exposure estimates are available for 6 of the 8 plants in the UAB study, and our exposure-response modeling is based on these 6 plants.…”
Section: Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…These 1995 data were updated in 2000 [5,6] to include substantially revised estimates of exposure. The most recent update of the data was in 2004, when the UAB added seven more years of follow-up (through 1998) and included the most recent estimates of exposures developed in 2000 [14,18]. Exposure estimates are available for 6 of the 8 plants in the UAB study, and our exposure-response modeling is based on these 6 plants.…”
Section: Analysesmentioning
confidence: 99%
“…The 2004 UAB study includes data on five non-exposure variables (age, years since hire, calendar year, race, and plant) and nine exposure variables (cumulative BD ppm-years, cumulative STY ppm-years, cumulative DMDTC mg/cm-years, cumulative number of BD high intensity tasks (HITs), cumulative number of STY HITs, cumulative ppm-years with BD 6100 ppm, cumulative ppm-years with BD >100 ppm, cumulative ppm-years with STY 650 ppm, and cumulative ppm-years with STY >50 ppm) that may have an effect on the endpoints analyzed. (Macaluso et al [14] describes the 100 ppm cutoff for BD and the 50 ppm cutoff for STY as ''. .…”
Section: Category Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported mean 8-hr TWA levels of styrene in air of glass-reinforced plastic facilities ranged from 3-82 ppm with individual 8-hr TWA levels up to B140 ppm. Some studies or reviews reported data indicating that generally styrene exposures have tended to decrease over time (Pfäffli and Säämänen, 1993;Welp et al, 1996;Macaluso et al, 2004). However, styrene exposures in the reinforced plastic facilities as reported by Lemasters et al (1985a) were essentially similar to the exposure levels reported by Lees et al (2003) and Luderer et al (2004).…”
Section: Summary Of Human Exposure Datamentioning
confidence: 83%
“…In a study reviewed by Harvard, maintenance workers in nonproduction departments of international paper mills were exposed to a mean TWA of 9.9 ppm styrene; the maximum value reported was 100 ppm and 4 of 93 TWA values exceeded 50 ppm. Macaluso et al (2004) estimated historical exposure to styrene in six North American styrene-butadiene rubber plants using a model that considered job tasks and factors affecting exposure potential (e.g., work practices, equipment used, exposure reduction mechanisms). Across all job categories, mean estimated TWA styrene exposures were within 2 ppm since the 1940s and declined to 0.5 ppm in the 1980s.…”
Section: Occupational Exposuresmentioning
confidence: 99%